2008
DOI: 10.1111/j.1460-9568.2008.06359.x
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin interacting protein 1 can regulate neurogenesis in Drosophila

Abstract: Huntington's disease (HD) is associated with a range of cellular consequences including selective neuronal death and decreased levels of neurogenesis. Ultimately, these altered processes are dependent upon proteins that interact with Huntingtin (Htt) such as the Huntingtin-interacting protein 1 (Hip1) which has a reduced binding preference to expanded Htt. These effects are similar to those observed with modified Notch signal transduction. As Hip1 plays a key role in endocytosis and intracellular transport, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…Even though Htt has not been found to directly interact with Notch, Hes1 or STAT3, our current findings do not rule out novel and indirect functional associations between these regulatory proteins. Indeed, recently reports have shown that: 1) Huntingtin interacting protein-1 (HIP1) can regulate Deltex-dependent Notch signaling for mediating neurogenesis in Drosophila [41] and 2) Hes1 is able to bind to STAT3 and to facilitate its expression and activation [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Even though Htt has not been found to directly interact with Notch, Hes1 or STAT3, our current findings do not rule out novel and indirect functional associations between these regulatory proteins. Indeed, recently reports have shown that: 1) Huntingtin interacting protein-1 (HIP1) can regulate Deltex-dependent Notch signaling for mediating neurogenesis in Drosophila [41] and 2) Hes1 is able to bind to STAT3 and to facilitate its expression and activation [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, one can associate the altered gene expression of γ-secretase components with abnormal proteolytic activity in HD (Tarlac and Storey, 2003 ). It was suggested that HTT-interacting protein HIP1 (huntingtin-interacting protein 1) may provide a functional link between non-canonical Notch signaling-mediated neurogenesis through a deltex -dependent pathway (Moores et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…As appropriate Notch expression levels are important to direct ESC differentiation to neural lineages [41], the apparent normal levels of expression of Notch and Hes5 in KO FGF2-responsive dNSs suggest that Htt may not play a role in the regulation of Notch signaling in dNSCs, and that alterations in neuronal and glial lineage elaboration may be due, in part, to additional non-redundant developmental signaling pathways. Thus far, Htt has not been shown to have any direct interaction with components of the Notch signaling cascade, with the exception of a single study reporting an indirect functional association between Huntingtin interacting protein 1 (HIP-1) and deltex-dependent Notch signaling in Drosophila that plays a role in neurogenesis [42]. Additional studies are required to elucidate the mechanisms underlying this regulatory function.…”
Section: Discussionmentioning
confidence: 99%